AKTIF BERTANYA SEBAGAI BENTUK ACTIVE LEARNING UNTUK MENINGKATKAN SCORE DALAM MENEMPUH MATA KULIAH STATISTIKA - Kafabih, Anim (Fokus ABDIMAS, 2025)
This article aims to describe the implementation of incentive-based active learning to encourage students to actively ask questions and express their opinions during statistics lectures. Incentives are given in the form of extra credit, which can influence scores on assignments and the final exam. The application of this strategy has been proven to improve conceptual understanding and learning outcomes, especially in statistics courses. The analysis shows that every question a student asks has a positive and significant effect on increasing their final exam score, for both male and female students, though the impact is greater for female students. These results confirm that active student involvement through questioning not only enriches the learning process but also provides measurable academic benefits. The success of this method is influenced by the consistent application of the rules, the provision of appropriate feedback, and the improvement in the quality of the questions asked. Therefore, strengthening strategies that can encourage both the quantity and quality of questions is key to increasing the effectiveness of active learning in the classroom. This finding contributes to the development of interactive learning methods that focus on active student participation as a means of improving academic achievement and conceptual understanding